Unsteady Hydromagnetic Couette Flow within Porous Plates in a Rotating System (Advances in Applied Mathematics and Mechanics, 2018)
Unsteady hydromagnetic Couette flow of a viscous incompressible electrically conductingfluid in a rotating system is studied when the fluid flow within the channel is induceddue to the impulsive movement of the one of the plates of the channel. The plates of thechannel are considered porous and the magnetic field is fixed relative to the moving plate.Exact solution of the governing equations is obtained by Laplace transform technique. Theexpression for the shear stress at the moving plate is also obtained. Asymptotic behaviourof the solution is analyzed for small as well as large values of time $t$ to highlight thetransient approach to the final steady state flow and the effects of rotation, magneticfield and suction/injection. It is found that suction has retarding influence on theprimary as well as secondary flow where as injection and time have accelerating influenceon the primary and secondary flows.